NATO: The Power of Partnerships
XII, 224 p.
Keywords: NATO has many European and global partner countries. The political and military utility of all these partnerships is clear; they 'provide' more security than they 'consume'. But the utility for NATO of partners also changes over time. This book scrutinizes these partnerships, both from a NATO perspective and from that of its partners.